PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN PERUSAHAAN DENGAN KUALITAS AUDIT SEBAGAI MODERASI - Ariel Leonardo; Dwi Ratmono (Diponegoro Journal of Accounting, 2023)
This research aims to analyze the impact of corporate social responsibility on financial performance, and to enhance the findings of this study, a moderating variable, which is audit quality, has been added. The sample tested in this study consists of non-financial companies listed on the Indonesia Stock Exchange from 2018 to 2021. The selected time frame takes into account the research objective, which is to compare the influence of CSR before and during the COVID-19 pandemic. Sample acquisition was carried out using purposive sampling as the sampling method based on specific criteria. The analysis method employed was Partial Least Square (PLS) with WarpPLS version 8.0 software as the analytical tool.The results of the research from 2018 to 2021 indicate that corporate social responsibility has a significant positive impact on financial performance, and audit quality alters the direction of the relationship between corporate social responsibility and financial performance. The sensitivity analysis results reveal differences in the impact before and during the COVID-19 pandemic.